2022
DOI: 10.3390/nu14193944
|View full text |Cite
|
Sign up to set email alerts
|

High Dietary Folic Acid Intake Is Associated with Genomic Instability in Peripheral Lymphocytes of Healthy Adults

Abstract: Mandatory fortification of food with synthetic folic acid (FA) was instituted in 1998 to reduce the incidence of neural tube defects. Adequate folate status is correlated with numerous health benefits. However, elevated consumption of FA is controversially associated with deleterious effects on health. We previously reported that excess FA mimicked folate depletion in a lymphoblastoid cell line. To explore the impact of FA intake from fortified food, we conducted an observational human study on 33 healthy part… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 82 publications
0
0
0
Order By: Relevance
“…In rodent studies, excess folate can be defined as exceeding the accepted standard baseline supplementation of 2 mg/kg diet. However, the optimal folate requirements for animals may be lower, and the activity of rate-limiting one-carbon metabolism enzymes is typically much higher in rodents compared with humans [20][21][22][23]. Chow diets fed to laboratory rodents can contain a variable amount of FA ranging from 2 to 15 mg/kg diet and averaging about 8 mg/kg diet [22].…”
Section: Defining Excess Folatementioning
confidence: 99%
See 2 more Smart Citations
“…In rodent studies, excess folate can be defined as exceeding the accepted standard baseline supplementation of 2 mg/kg diet. However, the optimal folate requirements for animals may be lower, and the activity of rate-limiting one-carbon metabolism enzymes is typically much higher in rodents compared with humans [20][21][22][23]. Chow diets fed to laboratory rodents can contain a variable amount of FA ranging from 2 to 15 mg/kg diet and averaging about 8 mg/kg diet [22].…”
Section: Defining Excess Folatementioning
confidence: 99%
“…Similarly, excess FA supplementation in rat dams (20 mg/kg diet) exacerbated weight gain and inflammation [123]. High folic acid exposure negatively impacted human lymphocyte stress response, genomic stability, and DNA methylation in both in vitro and in vivo conditions [21,124]. Others found that folic acid supplementation could promote a proinflammatory transcriptomic milieu in the colon [125,126] and that excess FA increased inflammation in response to a high-fat diet in rats [127].…”
Section: Excess Folate and Dysregulation Of The Immune Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…As summarised above, low FA intake results in adverse pregnancy outcomes. On the other hand, excess FA supplement consumption could induce genomic and epigenomic instability [63,64]. Although further studies on the human population is essential to estimate the true impact of high and low FA intake, it is highly likely that excess FA intake could also result in unfavourable outcomes.…”
Section: Genomic and Epigenomic Instabilitymentioning
confidence: 99%